Experimental evidence that host species composition alters host–pathogen dynamics in a ranavirus–amphibian assemblage. Issue 2 (1st December 2022) - Snyder, Paul W.; Ramsay, Chloe T.; Harjoe, Carmen C.; Khazan, Emily S.; Briggs, Cheryl J.; Hoverman, Jason Todd; Johnson, Pieter T. J.; Preston, Daniel; Rohr, Jason R.; Blaustein, Andrew R.
Abstract: Losses in biodiversity can alter disease risk through changes in host species composition. Host species vary in pathogen susceptibility and competence, yet how changes in diversity alter host–pathogen dynamics remains unclear in many systems, particularly with respect to generalist pathogens. Amphibians are experiencing worldwide population declines linked to generalist pathogens, such as ranavirus, and thus represent an ideal group to investigate how host species composition affects disease risk. We conducted experiments in which amphibian larvae of three native species (Pacific tree frogs, Pseudacris regilla ; Cascades frogs, Rana cascadae ; and Western toads, Anaxyrus boreas ) were exposed to ranavirus individually (in the laboratory) or as assemblages (in outdoor mesocosms). In a laboratory experiment, we observed low survival and high viral loads in P. regilla compared to the other species, suggesting that this species was highly susceptible to the pathogen. In the mesocosm experiment, we observed 41% A. boreas mortality when alone and 98% mortality when maintained with P. regilla and R. cascadae . Our results suggest that the presence of highly susceptible species can alter disease dynamics across multiple species, potentially increasing infection risk and mortality in co‐occurring species.